Complement as the enabler of carfilzomib‐induced thrombotic microangiopathy. (29th May 2020) - Blasco, Miquel; Martínez‐Roca, Alexandra; Rodríguez‐Lobato, Luis G.; Garcia‐Herrera, Adriana; Rosiñol, Laura; Castro, Pedro; Fernández, Sara; Quintana, Luis F.; Cibeira, María T.; Bladé, Joan; Fernández de Larrea, Carlos; Tovar, Natalia; et al.
Summary: Carfilzomib has been associated with the development of thrombotic microangiopathy (TMA) in relapsed/refractory multiple myeloma patients, a severe disease with no currently available aetiological treatment. We evaluated the potential role of terminal complement pathway in four patients with carfilzomib‐induced TMA. Membrane attack complex (C5b‐9) deposition on endothelial cells in culture exposed to plasma from patients during the acute phase of the disease suggests complement overactivation as a mechanism of potential endothelial damage in three out of four patients. If confirmed in larger cohorts, C5b‐9 evaluation will allow early identification of patients who could benefit from complement blockade and treatment monitoring.